Position of Natural Sciences in the Education of Reformed Higher Schools in the Hungarian Kingdom in Early Modern Age (on Example of Reformed Collegium in Sarospatak) - Annamaria Konyova (Communications - Scientific letters of the University of Zilina, 2017)
The Reformation, being one of the most significant streams of thought in the early modern age, was closely associated with considerable changes exhibited in various facets of life, also in the education. Transformation of schools to Protestant ones had a significant effect on the curriculum to some extent also in the use of innovative methods in education. The aim of this study is to show an important attribute of Reformed education, which started in early modern ages in the areas of Upper Hungary and manifested itself by strengthening the status of natural sciences in curriculum. The article focuses on a number of related problems. In the first place, I focus on a time horizon for implementing individual natural science courses in Reformed schools and their status amongst other courses. In addition, I pay attention to the research of the teaching method that was used at the time, the use of new methods, teaching aids, and mention the distinguished personalities that were essential during the process of development and implementation of these courses in schools, as well as other partial issues related to this.